Development of Flexible Antimicrobial Zein Coatings With Essential Oils for the Inhibition of Critical Pathogens on the Surface of Whole Fruits: Test of Coatings on Inoculated Melons - Boyacı, Derya; Yemenicioğlu, Ahmet; Iorio, Gianmarco; Sözbilen, Gözde Seval; Alkan, Derya; Trabattoni, Silvia; Pucillo, Flavia; Yemenicioğlu, Ahmet (Elsevier, 2019)
This study aimed to develop essential oil (EO)-containing antimicrobial coatings for the inhibition of pathogenic bacteria contamination on fruit peels. Incorporation of eugenol (EUG), carvacrol (CAR), and thymol (THY) into films at > 1% (w/w) eliminated the typical brittleness of zein films. However, EUG outperformed CAR and THY in terms of mechanical properties. Films with >= 2% (w/w) CAR and THY and >= 3% EUG showed clear zones against L. innocua and E. coli in agar medium at 37 degrees C. All EO-containing films also inhibited L. innocua and E. coli inoculated at their surfaces by minimum 3.9 and 2.7 decimal (D) within 1 day at 10 degrees C. Moreover, 2% EUG-containing zein coatings caused 2-3 decimal reduction in L. innocua and E. coli counts of inoculated melon surfaces at 10 degrees C. Unlike the bare zein coatings, flexible EUG-containing films on melons did not show cracking or detachment. Zein films loaded with EUG showed a highly hydrophilic surface. The best oxygen barrier performance was observed for the EUG-richest formulation (i.e., EUG at 3%), and this was attributed to a homogenizing effect of the EO that eventually led to a denser and hole-free network. This work suggested that flexible coatings of zein containing EOs could inhibit pathogens embedded in the rough peel surface of melons.
Keywords: Antimicrobial packaging; Edible coating; Edible film; Essential oil; Melon; Zein